Factors influencing smoking cessation success in an outpatient clinic: a cross-sectional study - Demir, Hasan Özcan; Eren, Furkan Alp; Mutlu, Hacer Hicran (Journal of Dependence, 2025)
Objective: Smoking remains a major global health issue, contributing to millions of preventable deaths annually. Effective smoking cessation strategies combine pharmacotherapy and behavioral support, yet real-world data on factors influencing treatment success in outpatient settings, particularly in Türkiye, are limited. The aim of this study was to evaluate the effectiveness of pharmacological treatment in a smoking cessation outpatient clinic and identify factors associated with cessation success. Method: This cross-sectional observational study included 203 adult smokers initiating pharmacological treatment at a tertiary hospital in Istanbul between April and October 2023. After excluding 22 patients lost to follow-up, 181 participants were analyzed. Data were collected via face-to-face interviews, the Fagerström Test for Nicotine Dependence (FTND), and 3-month follow-up calls. Bivariate analyses and multivariate logistic regression identified predictors of cessation success. Results: At 3-month follow-up, 28.6% of participants successfully quit smoking. Significant predictors of cessation included follow-up attendance (OR=0.18, p<0.001), lower nicotine dependence (OR=1.33, p=0.011), combination therapy (bupropion + nicotine replacement therapy; p=0.001), and employment status (OR=0.39, p=0.036). Age, gender, education, and income were not significantly associated with outcomes. Conclusion: Pharmacotherapy, particularly combination therapy, combined with follow-up visits and tailored to nicotine dependence levels, enhances smoking cessation success. Sustained behavioral support and adherence-focused strategies are critical for optimizing outcomes in clinical practice.